The Effect Of Fenugreek Plant On Improving Breastmilk Production In Mothers Nursing Infants Aged 0-6 - Riadini, Irma; Utami, VIda Wira; Nurliyani, Nurliyani; Keswara, Umi Romayati (Program Studi Kebidanan Fakultas Ilmu Kesehatan Universitas Malahayati, 2024)
World Health Organitasion ( WHO) merekomendasikan minimal pemberian ASI yaitu 50% (WHO, 2019).Kementrian Kesehatan menargetkan pemberian Asi ekslusif hingga 80%, Menurut data Riset Kesehatan Dasar (RISKESDAS) tahun 2021, tahun 2019 yang pada saat itu telah mencapai sebanyak 74,5% dari target capaian 80%.Data cakupan Dinas Kesehatan Kabupaten Lampung Utara sebanyak 55%, dari 65%, hasil dari data Pendekatan Keluarga Sehat (PIS-PK) pada tingkat Kecamatan Bunga Mayang sebanyak 67,74%, dan pada wilayah kerja Puskesmas Mulyorejo terdapat cakupan Asi esklusif sebanyak 45, 10%, dan cakupan Desa Mulyorejo 1 sebanyak 49,4%. Salah satu metode memperlancar ASI pada ibu dapat dilakukan melalui metode non farmakologi. Tujuan penelitian ini diketahui pengaruh kelabet dalam mamperlancar pengeluaran asi di Desa Mulyorejo 1 Kecamatan Bunga Mayang Kabupaten Lampung Utara Tahun 2023.Jenis penelitian kuantitatif, rancangan penelitan pra experimental dengan pendekatan one grouppretest-postest. Populasi penelitian ini adalah rata-rata ibu menyusui 0-6 bulan sebanyak 30 orang dengan sampel sebanyak 30 responden menggunakan teknik total sampling,analisis univariat dan bivariat ( uji wilcoxon).Hasil univariat didapatkan hasil rerata kelancaran pengeluaran asi pada berat badan mean 5364, standar deviasi 568,pada panjang badan mean 56,2 standar deviasi 4,5, lingkar kepala mean 38,8 standar deviasi 3,0.Analisis bivariat menunjukkan hasil pada berat badan mean 6538,3 standar deviasi 565,1, panjang badan mean 56,9 standar deviasi 4,5 lingkar kepala mean 39,4 standar deviasi 4,0 yang menunjukkan adanya pengaruh kelabet dalam mamperlancar pengeluaran ASI di Desa Mulyorejo 1 Kecamatan Bunga Mayang Kabupaten Lampung Utara Tahun 2023 (p-value = 0,000).Saran bagi ibu menyusi kelabet dapat dikonsumsi dalam Upaya menigkatkan produksi ASI. Kata Kunci : Produksi ASI, biji klebet, ibu menyusui ABSTRACT The World Health Organization (WHO) recommends a minimum of 50% breastfeeding (WHO, 2019). The Ministry of Health targets exclusive breastfeeding up to 80%. According to the Basic Health Research (RISKESDAS) data for the year 2021, in 2019, the rate reached 74.5% of the 80% target. The coverage data from the North Lampung Regency Health Office is 55%, from 65%. The results from the Family Approach to Healthy Living (PIS-PK) at the Bunga Mayang sub-district level are 67.74%, and in the working area of the Mulyorejo Public Health Center, exclusive breastfeeding coverage is 45.10%, with a coverage rate in Mulyorejo 1 village of 49.4%. One non-pharmacological method to facilitate breastfeeding is the use of fenugreek plant. The purpose of this study is to determine the influence of fenugreek Plant on improving breastmilk production in Mulyorejo 1 village, Bunga Mayang sub-district, North Lampung Regency, in the year 2023.This was a quantitative study with a pre-experimental design using a one-group pretest-posttest approach. The study population consisted of an average of 30 mothers breastfeeding infants aged 0-6 months, with a sample of 30 respondents using total sampling. Univariate and bivariate analysis (Wilcoxon test) was used for data analysis.Univariate results showed the average smoothness of breastmilk production in terms of weight, with a mean of 5364 and a standard deviation of 568; in terms of length, with a mean of 56.2 and a standard deviation of 4.5; and in terms of head circumference, with a mean of 38.8 and a standard deviation of 3.0. Bivariate analysis showed results for weight with a mean of 6538.3 and a standard deviation of 565.1, length with a mean of 56.9 and a standard deviation of 4.5, and head circumference with a mean of 39.4 and a standard deviation of 4.0, indicating the influence of fenugreek Plant on improving breastmilk production in Mulyorejo 1 village, Bunga Mayang sub-district, North Lampung Regency, in the year 2023 (p-value = 0.000). The recommendation for breastfeeding mothers is to consume fenugreek Plant to increase breastmilk production. Keywords: Breastmilk Production, Fenugreek Plant Seeds, Breastfeeding Mothers